2006
DOI: 10.1001/archneur.63.8.1090
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Stimulation in Parkinson Disease

Abstract: Background: Bilateral subthalamic high-frequency stimulation significantly improves motor functions in patients with advanced forms of Parkinson disease (PD). This favorable effect contrasts with a growing number of reports that the treatment may result in psychiatric complications.Objective: To analyze the presence of behavioral disorders and social maladjustment in PD patients successfully treated with continuous bilateral subthalamic stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(131 citation statements)
references
References 34 publications
8
112
1
9
Order By: Relevance
“…88 A higher-than-expected frequency of suicide has also been reported among patients undergoing STN DBS for advanced PD. 89 In a prospective study of 20 patients during the 2 years after surgery, however, Houeto et al 90 showed that provided patients with PD are rigorously selected for neurosurgery, STN stimulation improves mood, anxiety, and quality of life. The procedure does not result in severe permanent psychiatric disorders or modify patients' personalities, and it does not improve social function.…”
Section: Cognitive Side Effects Of Dbsmentioning
confidence: 99%
“…88 A higher-than-expected frequency of suicide has also been reported among patients undergoing STN DBS for advanced PD. 89 In a prospective study of 20 patients during the 2 years after surgery, however, Houeto et al 90 showed that provided patients with PD are rigorously selected for neurosurgery, STN stimulation improves mood, anxiety, and quality of life. The procedure does not result in severe permanent psychiatric disorders or modify patients' personalities, and it does not improve social function.…”
Section: Cognitive Side Effects Of Dbsmentioning
confidence: 99%
“…Nonetheless, changes attributed to DBS have included depression, 66 aggression, 11 hypomania, 42,73 mania, 122 apathy, 31,110 and inappropriate laughter. 65 In a prospective study of 20 patients with PD treated with subthalamic nucleus DBS, Houeto and colleagues 55 reported an improvement in depression severity of 21% at 6 months and 33% at 24 months. In contrast, a recent report by Berney and colleagues 12 found that acute DBS in a small series of 15 patients did not result in clinically significant mood alterations.…”
Section: Mood and Behavioral Effects Of Dbs For Movement Disordersmentioning
confidence: 99%
“…In contrast, a recent controlled study of 78 patients using a six-month follow-up reported depression in 5%, suicide in 1% and psychosis in 5%. 29 Potential mechanisms underlying psychiatric phenomena after DBS include pre-operative vulnerability, 63 stimulation, effects of surgery, psychosocial stressors and adaptation and alterations in medication after surgery. Stimulation in or around the STN has been observed to acutely lead to visual hallucinations, 64 pseudobulbar crying, 65 laughter and euphoria 4,66 and depression.…”
Section: Controversymentioning
confidence: 99%